Costs and benefits of food subsidies in India - George, Poykayil Simon (International Food Policy Research Institute, 1988)
Government interventions in foodgrain markets have existed in India in one form or another for about four decades, starting during the Second World War. Because supplies from Burma were cut off during the war, price controls and movement restrictions were introduced by the government; subsequently, other measures were added with a view to providing a minimum supply at subsidized prices. The major components of the government's food management policy over time have included procurement from domestic producers, monopoly imports, trade regulations, price controls, food distribution through fair-price shops, and buffer-stock operations (Chopra, 1981; Gupta, 1977; H. Knight, 1954; and Wall, 1978).